The role of religion in shaping contemporary man’s everyday moral character: an Islamic-Catholic perspective - Shehu, Fatmir Mehdi (2009)
The greatest problem that has confronted man since the beginning of his existence is the moral problem. Other problems (i.e., social, economic, political,religious, etc.) are only aspects of this master-problem. Man as a sound, rational and moral being, is always faced with the question: What are good and evil, right and wrong, moral and immoral acts? Therefore, this paper attempts to study the significant role of religion and its moral values in shaping man’s everyday aspect of character by promoting high moral principles to enable him to eliminate contemporary social ills. The shaping of man’s character is seen as an important issue by both religious groups of Islam and Catholicism. The Islamic-Catholic dictum - the promotion of good moral values and the abstention from evil values,will serve as a cornerstone for building the modern person’s everyday ethical aspect of character. A comparison between religious and irreligious moralities,the influence of Islamic-Catholic ethics towards secular thinking and the application of everyday ethics will be presented in the text of this paper, too. This paper reaches the following conclusions: (1) Religion plays a significant role in shaping contemporary people’s day-to-day intra-personal and inter-personal moral aspects of character and this will be actualized only when the process of ‘religionization’ of people’s everyday ethics will be taken seriously by people of sound reason; (2) Only religious or religionized ethics will enable humanity at large to solve contemporary problems.